Smooth particle hydrodynamics studies of wet granular column collapses - Wang, Guanjin; Riaz, Amir; Balachandran, Balakumar (Acta geotechnica, 2020)
Dry granular materials have been the subject of many investigations, while wet granular materials, which widely exist in many real-world applications, have only received limited attention. The aim of this paper is to address the missing gap in continuum modeling of wet granular materials. To study the wet granular flows, a grain-scale capillary interaction is introduced, as additional cohesive stress in the continuum-scale framework. We coupled the viscoplastic constitutive law for dry granular material and cohesion model for wet isotropic granular material to capture the behavior of wet granular materials. This combined model is implemented in a smooth particle hydrodynamics framework because the meshfree nature of this method captures the large deformation of granular flows without local grid distortion. The Wendland kernel is used as the interpolation kernel to improve numerical stability. This framework is validated by comparing numerical results with recent experimental findings for both dry and wet cases. The comparisons are illustrative of the potential of the framework to capture the behavior of granular materials across different phases. For different levels of friction and water content, the run-out dynamics and shear strength properties of granular materials in the final quasi-static regime are investigated. For granular flows on flat surfaces, compared with dry granular materials, with the introduction of surface tension in wet granular materials, it is found that there are increases in shear stresses locally and globally, enabling stronger internal forces to support structures with larger angles of repose. The surface energy-induced cohesion is found to play an important role in low friction cases compared to high friction cases. To benchmark the numerical framework presented here, granular column collapses on curved surfaces are also investigated. For flows on curved surfaces, although there are also increases in internal shear stresses, the differences in final profiles between wet granular materials and dry granular materials are not as pronounced as that on flat surfaces due to geometric constraints. The findings of this work are demonstrative of the capabilities of the smooth particle hydrodynamics method for the study of wet granular materials. This effort can serve as a step forward in the quest for a unified continuum theory and computational framework of granular material dynamics.